Empowering Women Through Technology: Social Transformation in Education and Economic Empowerment - Ruhana, Faria; Irwandi; Hoerudin, Cecep Wahyu; Dharmawati, Tuti; Ashfan, Mahadharu Ashifaati (Global Writing Academica Researching & Publishing, 2023)
The development of information and digital technology has opened up new opportunities to increase the role of women in various aspects of life. However, inequality in access and use of technology is still a serious obstacle that needs to be overcome. Empowering women through technology is the key to creating a more inclusive and sustainable society. This research aims to investigate the role of technology in women's empowerment with a focus on social transformation, participation in the online world, and strategies for overcoming inequality. The descriptive qualitative research method is used by collecting data from the results of previous research and studies and then analyzing it systematically. The results of this research show that women, with increased digital literacy, can take a more active role in utilizing technology to improve their well-being. Inclusive policies and support for women's involvement in technology professions are key to overcoming inequality. In conclusion, technology integration is key to women's empowerment, and a holistic strategy is needed to achieve a more inclusive and sustainable society.